→Answer:
y = -17
→Step-by-step explanation:
Well first off the f(x) in the equation f(x) = 3x + 7 can also be written as y,
y = 3x + 7
So if x is -8 we need to plug it in for x and solve, simple as that :)
y = 3(-8) + 7
y = -24 +7
y = -17
Answer:
1) A 1 1/3 2) C 1 5/12
Step-by-step explanation:
1) 2/6+4/8+5/10
Reduce 4/8 with 4 and 5/10 with 5.
2/6+1/2+1/2
Reduce 2/6 with 2.
1/3+1/2+1/2
Add fractions with a common denominator.
1/3+2/2
Reduce 2/2 with 1
1/3+1
Write all numerators above the common denominator.
1+3/3
Calculate.
4/3 = 1 1/3
2) 2 3/4 - 1 1/3
Change to improper fractions.
11/4 - 4/3
Write all numerators above the common denominator.
33-16/12
Calculate.
17/12 = 1 5/12
Hope this helps :)